Mechanical and Underwater Acoustic Properties of the Polyurethane Elastomers with Different Hard Segment Contents. Issue 1 (April 2019) - Li, Xiaohui; Xing, Suli; Yang, Jinshui; Yin, Changping; Ju, Su
Abstract: Polyurethane elastomers with different hard segment contents were synthesized by one-step method, using polypropylene glycol (PPG) as soft segment, toluene diisocyanate (TDI) and triethanolamine (TEA) as hard segments. The effects of hard segment content on the molecular structure, mechanical properties and underwater acoustic properties of polyurethane elastomers were studied. The results showed that hard segment contents have a great impact on mechanical and underwater acoustic properties of the PUs obtained, the tensile strength, hardness and compressive strength increased with the growth of the hardness segment contents, and sample with 20 wt% has the best underwater acoustic properties, whose α can reach at 0.7.